TANDEM ZINC-FINGER/PLUS3 Is a Key Component of Phytochrome A Signaling. Issue 4 (27th March 2018) - Zhang, Shaoman; Li, Cong; Zhou, Yangyang; Wang, Xiaoji; Li, Hong; Feng, Ziyi; Chen, Haodong; Qin, Genji; Jin, Dan; Terzaghi, William; Gu, Hongya; Qu, Li-Jia; et al.
Abstract : TZP is a positive regulator of phyA signaling and is required for the formation of a phosphorylated nuclear form of phyA in far-red light. Abstract: Phytochrome A (phyA) is the primary plant photoreceptor responsible for perceiving and mediating various responses to far-red (FR) light and is essential for survival in canopy shade. In this study, we identified two Arabidopsis thaliana mutants that grew longer hypocotyls in FR light. Genetic analyses showed that they were allelic and their FR phenotypes were caused by mutations in the gene named TANDEM ZINC-FINGER/PLUS3 ( TZP ), previously shown to encode a nuclear protein involved in blue light signaling and phyB-dependent regulation of photoperiodic flowering. We show that the expression of TZP is dramatically induced by light and that TZP proteins are differentially modified in different light conditions. Furthermore, we show that TZP interacts with both phyA and FAR-RED ELONGATED HYPOCOTYL1 (FHY1) and regulates the abundance of phyA, FHY1, and ELONGATED HYPOCOTYL5 proteins in FR light. Moreover, our data indicate that TZP is required for the formation of a phosphorylated form of phyA in the nucleus in FR light. Together, our results identify TZP as a positive regulator of phyA signaling required for phosphorylation of the phyA photoreceptor, thus suggesting an important role of phosphorylated phyA in inducing the FR light response.